ANALISIS PENGARUH LIKUIDITAS, LEVERAGE, DAN PROFITABILITAS TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (Students' Journal of Economic and Management, 2014)
The purpose of the research is to examine the effect of liquidity, leverage, and profitability on dividend payout ratio. This research is focused on manufacturing company at Indonesia Stock Exchange during the period 2009, 2010, and 2011.In this study, researchers used purposive sampling and obtain a sample of 39 sample companies. The analysis data use multiple regression model. The result show that Liquidity (Cash Ratio) has positive and no significant effect, Leverage (Debt to Equity Ratio) has negative and significant effect, and than Profitability (ROE) has positive and no significant effect. The Adjusted R Square is 0,220. It means that 22% variation of Dividend Payout Ratio influenced by the Cash Ratio, DER, and ROE, while the rest of 78% influenced by other factors which are not included in the model. Keyword: Cash Ratio, DER, ROE, and Dividend Payout Ratio